Hearing the Future The Music and Magic of the Sanguma Band - Crowdy, Denis (Music and Performing Arts of Asia and the Pacific, 2016)
As the optimism of the early years of the nation faded due to harsh economic and social realities, and as an increasingly commercial popular music scene came to dominate public music culture, tensions between a once heard future and the sounding present emerged. Continuing a theoretical trajectory in ethnomusicology, Crowdy explores the role of music in imagining, constructing, and representing national and regional identity. The analysis reveals inherent tensions between distinctly Melanesian ideals and the complexities in navigating the realities of local neoliberal capitalism